Penegakan Hukum terhadap Tindak Pidana Korupsi Dana Bantuan Sosial Pandemi Covid-19 yang dilakukan oleh Pejabat Negara - Ni Komang Sri Herawati Octa; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Jurnal Preferensi Hukum, 2022)
Indonesia is a legal state (Rechtsstaat) not based on mere power (Machtstaat). Weak law enforcement in Indonesia causes crimes such as corruption in social assistance funds among state officials to increase. The purpose of this research is to analyze the regulation of corruption in social assistance funds and to discuss law enforcement of criminal acts of corruption in social assistance funds in an effort to recover state losses. This type of research is normative research, using a statutory approach and a conceptual approach. Sources of legal materials consist of primary and secondary materials. The technique in collecting legal materials with data collection is by quoting than in the data in a freelance record by recording the name of the author, book title, publisher name, publisher year, and page number quoted. The regulation of criminal acts of corruption in social assistance funds carried out by state officials is regulated in Article 3 of Law No. 20 of the Year with the threat of life imprisonment or imprisonment between 1 to 20 years and a fine as stipulated in this article. Sanctions for criminal acts of corruption in an effort to recover state losses are regulated in Article 18 Paragraphs (1) and (2) of Law No. 20 of 2001 concerning the Eradication of Criminal Acts of Corruption. Law enforcers are expected to give the fairest sanctions to the perpetrators according to their actions so that these sanctions are beneficial for the perpetrators and the injured party.